The Customersâ Determinant Factors Of The Bank Selection - Krisnanto, Umbas (Universitas Prasetiya Mulya, 2011)
SomeÂ previousÂ researchersÂ are stillÂ arguingÂ about the factorsÂ that determineÂ the selection ofÂ aÂ bank. These factorsÂ depend onÂ the intensity of marketing activitiesÂ undertakenÂ by theÂ bank,Â reputation of the bank, credit availability, friendly staffs, appropriate interest rates, andÂ location. JakartaÂ wasÂ selected for the research location since Jakarta is the biggest city in Indonesia that represents the advancement of the banking industry. Different statistics tools are applied to find the accurate opinion why respondent choose a bank. Based on the results, the research concludes factors that determine in selecting a bank tend to be based on the secondary factors such as recommendation from friends, and advice from family members.DOI :Â https://doi.org/10.21632/irjbs.4.1.59-70Keywords:Bank Marketing